Chromosomal evolution and phylogenetic considerations in cuckoos (Aves, Cuculiformes, Cuculidae) - Santos, Michelly da Silva dos (Public Library of Science, 2020)
The Cuckoos have a long history of difficult classification. The species of this order have been the subject of several studies based on osteology, behavior, ecology, morphology and molecular data. Despite this, the relationship between Cuculiformes and species of other orders remains controversial. In this work, two species of Cuculidae, Guira guira (Gmelin, 1788) and Piaya cayana (Linnaeus, 1766), were analyzed by means of comparative chromosome painting in order to study the chromosome evolution of this group and to undertake the first chromosome mapping of these species. Our results demonstrate high chromosomal diversity, with 2n = 76 in G. guira, with fission and fusion events involving ancestral syntenies, while P. cayana presented only fissions, which were responsible for the high diploid number of 2n = 90. Interestingly, there were no chromosomal rearrangements in common between these species. Our results, based on Giemsa staining, were compared with previous data for other cuckoos and also with taxa proposed as sister-groups of Cuculiformes (Otidiformes, Musophagiformes and Opisthocomiformes). Cytogenetic comparisons demonstrated that cuckoo species can be divided into at least three major groups. In addition, we found no evidence to place Cuculiformes close to the groups proposed previously as sister-groups.